DIGITAL RELIGION PADA INSTITUSI MASJID DI ERA MEDIA DIGITAL - Alya Jasmine; Nurist Surayya Ulfa (Interaksi Online, 2026)
The rapid expansion of digital media has opened new possibilities for religious institutions to extend their reach beyond physical boundaries. This study examines how Jogokariyan Mosque in Yogyakarta navigates the digital media landscape as a case of how an Islamic institution engages with digital religion. Using a qualitative case study approach, this paper describes how the mosque has situated itself in the digital media environment while preserving its core religious functions. The study finds that the mosque's engagement with digital media operates as an extension of its physical mission rather than a departure from it. These findings contribute to the broader discourse on how local Islamic institutions position themselves within the evolving digital media ecosystem.